Quasar luminosity function: a point processes approach (Publicaciones en Ciencias y Tecnología, 2018)
The quasar luminosity function measures the number of quasars per cubic megaparsec and absolute magnitude. It is one of the most important tools for studying the active galactic nucleus population and how they have evolved in time. Our investigation estimates this function through a probabilistic approach. We model the observed density of quasars using a bidimensional non-homogeneous Poisson Process in the space of absolute magnitude times redshift. A series of adjustable parametrized models are tested and we use maximum likelihood and the Bayesian Information Criteria (BIC) to select the best model, from wich the corresponding quasar luminosity function is obtained. Finally a residual analysis is made to study the goodness of fit.
Keywords: Point process; active galactic nucleus; non-homogeneus Poisson process